High sensitivity surface plasmon resonance (SPR) refractive index sensor in 1.5 μm - Ahmad, Harith; Amiri, I.S.; Soltanian, M.R.K.; Narimani, L.; Zakaria, Rozalina; Ismail, Mohammad Faizal; Thambiratnam, K. (American Scientific Publishers, 2017)
A surface plasmon resonance (SPR) based sensor is proposed and demonstrated for operation in the 1500 nm region. The sensor operates by the immersion of microfibers with a 25-μm diameter waist in chemical solutions that have varying external effective refractive indices. The sensor is fabricated using a homemade single-mode tapered fiber with a uniform waist coated on all sides with a gold layer approximately 45 nm thick by means of a vacuum electron beam evaporator machine. The transmission dips in the sensor’s optical spectrum are highly responsive to any perturbations in the external medium refractive index, thus providing high sensitivity. The proposed sensor system has multiple potential applications in biological and chemical constituent and reaction measurements.